Identification of molecular alterations in neurotransmission and synaptic genes in Autism Spectrum Disorder - Vilela, Joana (2019)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder, which affects brain function. It is characterized by the presence of social communication deficits and restricted, repetitive patterns of behavior. ASD has a strong genetic component and there is evidence in support of many putative risk genes. However, the genetics and the biological processes underlying the disease are still incompletely understood and will require the integration of intermediate phenotypic analysis provided by direct observation tools such as brain imaging.